(untitled) (University Arena, 2025)
The individualization of tennis coaching is based on the process of getting to know each player’s individuality and, based on this line of reasoning, the most appropriate methods and means of preparation will be chosen and applied to achieve the expected objectives. Researching all the individual characteristics will help to know and understand the needed elements (attributes or shortcomings) that underlie an athlete’s success. The more complex, the more solid and useful our knowledge will be, based on modern research methods pertaining to the performance-specific requirements of the tennis game.